Marital status and the prevalence of obesity in a Korean population. Issue 3 (May 2020) - Lee, Jeeyoo; Shin, Aesun; Cho, Sooyoung; Choi, Ji-Yeob; Kang, Daehee; Lee, Jong-Koo
Highlights: We investigated the association between obesity and abdominal obesity indices and marital status in a large Korean population. Married participants showed a higher prevalence of obesity and abdominal obesity than those in other marriage categories except for widowed women. This investigation suggests that obesity and abdominal obesity vary according to marital status. Abstract: Objective: Previous studies have reported on marital status and the prevalence of obesity; however, few studies have assessed the prevalence of underweight in relation to marital status. This study aimed to explore the association of obesity and abdominal obesity with marital status among Koreans aged 40–69 years. Methods: We selected a total of 137, 608 participants from the Health Examinees Gem Study for the final analysis. Multinomial logistic regression models were used to estimate odds ratios (OR) and their 95% confidence intervals (CI) for the association of obesity with marital status, with controlling for potential confounders. Results: The prevalence of underweight was higher in unmarried men (OR: 1.82, 95% CI: 1.25–2.63) and women (OR: 2.16, 95% CI: 1.79–2.61) than in married individuals. Compared to married individuals, a lower prevalence of BMI ≥ 25 kg/m 2 was observed for those who were unmarried (men: OR: 0.71, 95% CI: 0.62–0.81, women: OR: 0.65, 95% CI: 0.58–0.73) or divorced/separated (men: OR: 0.80, 95% CI: 0.69–0.93, women: OR: 0.90, 95% CI: 0.83–0.98). Interestingly, widowed women showed higher prevalence of BMI ≥ 25 kg/m 2 (OR: 1.17, 95% CI: 1.10–1.25) and abdominal obesity (OR: 1.23, 95% CI: 1.16–1.30) compared to married women, and the association persisted only among women in their 50s and 60s. Conclusions: Married participants showed a higher prevalence of obesity and abdominal obesity than those in other marriage categories except for widowed women.